Design of 3D Animation Application on STIKOM Dinamika Bangsa Jambi - Rico, Rico; Benny, Benny (-)
The 3D animation is a 3D visualization or a 3D animated video that embodies the idea visually to solve a problem that suits the needs. In the current development of 3D animation can be used for as a medium to create a graphic design of a building for promotional purposes and so forth. Regarding the promotion or introduction, STIKOM Dinamika Bangsa Jambi campus has not implemented 3D animation and still uses manual way through presentation, and photographs about facilities and infrastructure facilities contained in STIKOM Dinamika Bangsa Jambi, so there are still many people do not know the facilities Found on STIKOM Dinamika Bangsa Jambi. Therefore, in this research will be built a 3D animation application that is useful to explore all areas and facilities that are found in STIKOM Dinamika Bangsa Jambi.